Diffuse idiopathic skeletal hyperostosis: a rare cause of dysphagia and dysphonia. (23rd April 2013) - Fox, Thomas Peter; Desai, Mihir Kumar; Cavenagh, Tom; Mew, Edward
Abstract : This article reports on the case of a 63-year-old Jamaican man who presented with progressive dysphagia and dysphonia. CT was able to visualise several large anterior cervical osteophytes, which were protruding into soft tissue structures such as the pharynx and oesophagus. Surgical removal of C3–C6 was undertaken but severe damage to local structures had already occurred. The patient remained nil by mouth and had a percutaneous gastrostomy feeding tube for means of nutrition. Four months later, despite the removal of the osteophytes, videofluoroscopy demonstrated that the patients swallow remained unsafe. The patient suffered three episodes of aspiration pneumonia and although their speech improved, they remain nil by mouth at the time of going to publication.